Yarsagumba [Cordyceps sinensis (Berk.) Sacc.]; Traditional Utilization in Dolpa District, Western Nepal - Devkota, S. (Our Nature, 2007)
Cordyceps sinensis (Berk.) Sacc., a well-known and valued traditional medicine, is also called winter worm summer grass. The product deserves high potential to generate income opportunities, enhance rural income and raise the national revenue. The study of C. sinensis was carried out in Dolpa district, Western Nepal to document ethnomycological uses and local practices. Data were collected using open ended questionnaires administered to collectors/users (n = 74), traders (n = 25) and local healers or amchis (n = 3). Indigenous peoples are utilizing this Himalayan treasure for the treatment of different diseases like diarrhea, headache, cough, rheumatism, liver disease, and also as an aphrodisiac and tonic. Internationally it is regarded as Himalayan Viagra. The present study therefore aims at highlighting the ethnomycological uses of C. sinensis resource of the Trans-Himalayan region in their niche. Key words: Cordyceps, Dolpa, Ethnomycology, Nepal doi:10.3126/on.v4i1.502 Our Nature Vol. 4(1) 2006 pp48-52